Using Serum Metabolomic Signatures to Investigate Effects of Acupuncture on Pain-Fatigue-Sleep Disturbance in Breast Cancer Survivors - Hongjin Li; Ardith Z. Doorenbos; Yinglin Xia; Jun Sun; Hannah Choi; Richard E. Harris; Shuang Gao; Katy Sullivan; Judith M. Schlaeger (Metabolites)
Background/Objectives: Acupuncture is an efficacious integrative therapy for treating pain, fatigue, and sleep disturbance (the psychoneurological symptom cluster) in breast cancer survivors. However, the mechanisms underlying its effects remain unclear, and related metabolomics studies are limited. This study aimed to examine serum metabolite changes after acupuncture and their relationships to symptom improvement. Methods: Forty-two breast cancer survivors experiencing pain, fatigue, and sleep disturbance participated in a single-arm acupuncture trial. They received a 10-session acupuncture intervention over 5 weeks. Fasting blood samples and symptom surveys were collected before and after the acupuncture intervention, and untargeted metabolomics profiling was conducted on serum samples. Mixed-effects models adjusting for covariates (age, race, body mass index, and antidepressant use) were applied for analysis. Results: After acupuncture, there was a significant reduction in the psychoneurological symptom cluster (mean reduction = −6.2, p < 0.001).Bonferroni correction was applied to 40 independent metabolite clusters (α = 0.00125); cysteine-glutathione disulfide (p = 0.0006) significantly increased, and retinal (p = 0.0002) and cis-urocanate (p = 0.0005) were significantly decreased. Dimethyl sulfone (p = 0.00139) showed a trend towards reduction after acupuncture and its change (p = 0.04, β =1.97) was positively associated with reduction in the psychoneurological symptom cluster. Also, increased lauroylcarnitine (p = 0.0009) and decreased cytosine (p = 0.0008) can modulate the therapeutic effects of acupuncture. Conclusions: Acupuncture demonstrates beneficial effects on the psychoneurological symptom cluster in breast cancer survivors. Dimethyl sulfone may be a promising mediator in the relationship between acupuncture and psychoneurological symptoms, while acylcarnitine metabolism may modulate the therapeutic effect of acupuncture.